Peningkatan Prestasi Belajar Mata Pelajaran Matematika Materi Pembagian menggunakan Papan Pembagian Siswa Kelas IV SD Negeri Sumowono - Akrom, As’Adun; Winarti, Puji; Sri Legowo, Yogi Ageng (WASPADA (Jurnal Wawasan Pengembangan Pendidikan), 2023)
This study was motivated by the low value of mathematics subjects in division material in class IV at SD Negeri Sumowono. The formulation of the problem in this study is how to improve student learning achievement in learning math division material in Class IV SD Negeri Sumowono using a division board. The purpose of this study was to improve learning achievement in mathematics subject of division using division board.The research subjects were all fourth grade students of SD Negeri Sumowono which amounted to 26 students. This research was conducted in March of the 2022/2023 academic year. In this study, 2 data collection techniques were used, namely: (1) Tests to determine the value of student learning outcomes; (2) Observations made during the learning process to determine teacher skills and student activities.The results of the research were an increase in learning achievement as indicated by the results of the evaluation test in cycle I, which was completed by 11 students (42.30%), in cycle II it increased to 22 students (84.61%). For teacher skills, he received a score of 77.5 (Good) in cycle I and increased to 90 (very good) in cycle II. Student activity increased in the very good category from no students getting a very good score (0%) to 4 students getting a very good score (15.39%). Thus, it can be concluded that there is an increase in achievement in mathematics in division material using division boards in class IV students at Sumowono State Elementary School.Keywords: Mathematics, Division Material using the Division Board.